"Measuring the factors affecting Job Characteristics with Personal outcomes" (A Case Study of Khairpur Sugar Mill). (2019) - Lashari, Aamir Ali; Shah, Imran Ahmed; Malkawy, Sahira; Parveen, Shahdma
No abstract available